LETTING GO OF THE HUMANITARIAN PRINCIPLES IN COMPLEX EMERGENCIES? A CASE STUDY OF CIVIL-MILITARY COOPERATION IN THE EASTERN DEMOCRATIC REPUBLIC OF CONGO - MUSEKA, Nickson Bondo (Studia Universitatis Babes-Bolyai Studia Europaea, 2024)
Civil-military cooperation (CIMIC) has officially emerged as a coordinated strategy between the United Nations peacekeeping missions and humanitarian non-governmental organizations (NGOs) to enable access to people in need of assistance in complex emergencies. However, this integrated approach raises serious concerns regarding the respect of traditional principles of humanitarian action: humanity, impartiality, neutrality, and independence. While some humanitarian NGOs are opposed to any form of collaboration with the military, others believe this cooperation is very important to enable access and provide aid to civilians in needs. Using the case study of the Democratic Republic of Congo (DRC), this article analyses the impact of the CIMIC integrated approach between the United Nations Peacekeeping and Stabilization Mission in the DRC (MONUSCO) and humanitarian NGOs on the afore-mentioned principles of humanitarian action. It argues that most humanitarian NGOs that are operating in the Eastern DRC are opposed to the CIMIC’s integrated approach as it pushes them to violate the principles of neutrality, independence, and impartiality. Second, CIMIC increases the danger of humanitarian workers to be targeted by illegal armed groups. Third, despite their integrated approach, both MONUSCO and humanitarian actors have not been able to pacify the Eastern DRC, end the humanitarian needs of the population, or improve their effectiveness.